PENGEMBANGAN INSTRUMEN HOTS FIKIH BERBASIS SOCIO-SCIENTIFIC ISSUES UNTUK PENGUATAN PENALARAN ETIS - Dilla Muckti Jihansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop and examine the feasibility of a Higher Order Thinking Skills (HOTS) test instrument for the subject of Fiqh on the topic of Ikhlasul Amal (slaughtering, sacrificial offering/qurban, and aqiqah), designed based on a socio-scientific issues (SSI) approach to strengthen students' ethical reasoning. The instrument consists of 35 multiple-choice items and 5 essay items constructed around contextual cases such as ostentation (riya') in performing qurban, unequal distribution of sacrificial meat, and social pressure in religious practice, requiring students to analyze, evaluate, and create solutions (cognitive levels C4-C6) rather than merely recall textual fiqh rulings. This Research and Development (R&D) study involved a limited trial with 25 ninth-grade students at MTsN 5 Magetan. The instrument's feasibility was examined through content validity (Aiken's V) by five expert validators, empirical item validity (product moment correlation), reliability (Cronbach's Alpha), normality testing (Shapiro-Wilk), and classical item analysis using Iteman 4.3. Results show that all 35 items obtained Aiken's V indices between 0.80 and 1.00 (very valid category), all items were empirically valid (r-count 0.463-0.782 > r-table 0.396), the instrument was highly reliable (α = 0.959), and student score data were normally distributed (Shapiro-Wilk Sig. = 0.077). Nonetheless, classical item analysis revealed eleven items with low to negative discrimination indices (Rpbis), indicating the need to revise certain distractors. Overall, the instrument is considered feasible for measuring students' higher order thinking skills and ethical reasoning on the topic of Ikhlasul Amal, with recommended revisions to several items prior to wider-scale use